2020
DOI: 10.3126/jgmcn.v13i1.28973
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and antimicrobial susceptibility patterns of wound infections among adult patients attending Gandaki Medical College Teaching Hospital, Nepal

Abstract: Introduction: Wound infections are significant group of infections in the hospitals worldwide. The wide spread uses of antimicrobial agents lead to emergence of resistant pathogens contributing to increased morbidity and mortality. Accurate and prompt antimicrobial therapy is required to reduce the complications. This study was aimed to investigate pyogenic bacterial pathogens and their susceptibility patterns. Methods: A cross sectional study was carried out at Gandaki Medical College Teaching Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Another possible mechanism is enhanced esterification of fatty acids at the hepatic level [17]. The HDL-C was significantly higher in the euthyroid group than in the subclinical hypothyroidism group, which is in agreement with Karthick et al [17], James et al [20], Caron et al [34], and Erdem et al [35] but contradicts Regmi et al, who found increased HDL-C in the subclinical hypothyroid population compared to normal euthyroid females [36]. However, some studies did not show any significant difference in HDL-C between euthyroid and subclinical hypothyroid females [20].…”
Section: Discussionsupporting
confidence: 67%
“…Another possible mechanism is enhanced esterification of fatty acids at the hepatic level [17]. The HDL-C was significantly higher in the euthyroid group than in the subclinical hypothyroidism group, which is in agreement with Karthick et al [17], James et al [20], Caron et al [34], and Erdem et al [35] but contradicts Regmi et al, who found increased HDL-C in the subclinical hypothyroid population compared to normal euthyroid females [36]. However, some studies did not show any significant difference in HDL-C between euthyroid and subclinical hypothyroid females [20].…”
Section: Discussionsupporting
confidence: 67%
“…In the current study, the overall culture positivity rate from patients with surgical site infection was 71.7%, which was slightly higher than results previously reported from India (68%) [ 28 ], but lower than a report from Mekelle (75%) [ 29 ] and Nigeria (82%) [ 30 ]. Lower rates of positive culture were reported from India (50%) [ 31 ] and Nepal (63.3%) [ 16 ], Bangladesh (61.8%) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common microorganism cultured from SSIs is Staphylococcus aureus [ 14 16 ]. When a viscus, such as the large bowel, is opened, tissues are likely to be contaminated by numerous organisms.…”
Section: Introductionmentioning
confidence: 99%